1997
DOI: 10.1089/thy.1997.7.885
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients with Graves' Ophthalmopathy is Markedly Decreased: Measurement by the Medical Outcomes Study Instrument

Abstract: To assess the impact of Graves' ophthalmopathy (GO) on quality of life using a general questionnaire, we performed a descriptive study on consecutive ophthalmopathy patients. We included 70 consecutive, euthyroid patients (age >18 years, 50 females, 20 males, mean +/- SD age 53 +/- 13 years) with varying degrees of severity of GO. General quality of life was assessed with the brief survey (24 questions) from the Medical Outcomes Study (MOS-24), and three subscales of the Sickness Impact Profile (SIP). In compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
128
0
12

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(146 citation statements)
references
References 15 publications
6
128
0
12
Order By: Relevance
“…Não houve diferença da auto-estima entre os pacientes dos subgrupos leve e moderado-grave Os dados objetivos nem sempre correspondem com a condição percebida pelo paciente. Pacientes com condições objetivamente idênticas descrevem o seu status de saúde de maneira diferente (3) . Outros estudos com doenças crônicas também encontraram pouca relação entre as medidas clínicas e os resultados dos escores da qualidade de vida (3,(37)(38) .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Não houve diferença da auto-estima entre os pacientes dos subgrupos leve e moderado-grave Os dados objetivos nem sempre correspondem com a condição percebida pelo paciente. Pacientes com condições objetivamente idênticas descrevem o seu status de saúde de maneira diferente (3) . Outros estudos com doenças crônicas também encontraram pouca relação entre as medidas clínicas e os resultados dos escores da qualidade de vida (3,(37)(38) .…”
Section: Discussionunclassified
“…Na maioria das vezes está associada à doença de Graves, entretanto, manifestações oculares similares também podem ocorrer, com menor freqüência, em pacientes portadores de tireoidite de Hashimoto, hipotireoidismo ou até mesmo em pacientes eutireoideanos (1)(2) . A enfermidade inicia-se com um processo inflamatório induzido pela reação auto-imune, cuja duração poderá variar de meses a anos, seguindo-se de fase crônica, caracterizada pelo acúmulo de tecido fibroso nos músculos extra-oculares, e também nos tecidos adiposo e conectivo retrobulbar (3)(4) . Dentre os diversos sinais observados poderão estar presentes a proptose, disfunção dos músculos extra-oculares, alterações dos tecidos moles, e também déficit visual por neuropatia compressiva e ceratite por exposição (5) .…”
unclassified
See 1 more Smart Citation
“…Based on the most frequently observed symptoms and questionnaires found in the international literature (Medical Outcomes Study-24 questionnaire [13]; Short Form-36 questionnaire [14]; EuroQol VAS Questionnaire [15]; National Eye Institute Visual Function Questionnaire [16]; Profile of Mood States [17]; Graves' ophthalmopathy Quality of Life Questionnaire-GOQOL [18]), we developed a questionnaire to measure the HRQOL in patients who had undergone total thyroidectomy for GD. Many of the questions included in our questionnaire were derived from these previously cited studies and were thus considered to be validated.…”
Section: Questionnairementioning
confidence: 99%
“…3 The management of GO has been well studied previously, but the impaired quality of life (QOL) caused by GO has been the focus of recent attention. 4 QOL of patients with GO was investigated using a health questionnaire (Medical Outcome Study Short-Form General Health Survey and Sickness Impact Profile) by Gerding et al 4 The study showed little correlation between measures of activity or severity of disease and the scores on the QOL questionnaire. The authors reported that patients with mild or moderately severe GO had similar or worse QOL impairment than patients suffering from heart failure, pulmonary emphysema, or diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%